Servant leadership and absenteeism in Reykjavík´s thermal pools - Eva-Charlotte Haensel 1983- (2020)
Although servant leadership has been widely found to improve employees´ well-being and employee´s well-being has been often named as determinant of absenteeism, the effect of servant leadership on absenteeism has been very little researched previously. Thus, a quantitative analysis was performed in the thermal pools of Reykjavík to test a structural model that proposed that servant leadership reduces absenteeism through the mediation of job satisfaction and self-perceived health. Pools of Reykjavík where the director was perceived to be more of a servant leader were found to have more satisfied employees. Results at the individual pool employee´s level supported the proposed model. On the one hand, a positive correlation was found between servant leadership and job satisfaction as well as better self-perceived health. On the other hand, a negative correlation was found between absenteeism and job satisfaction as well as self-perceived health. Moreover, the path from servant leadership through increased job satisfaction to decreased absenteeism could be confirmed with binary logistic regression and mediation analysis. The findings of this research are of practical value to performance orientated managers as they show that servant leadership can reduce absenteeism and therefore reduce salary costs and improve the bottom line. This research is of scientific value as it is one of the first studies that link servant leadership to accountably measurable results and proposes a structural model of how servant leadership effects absenteeism that could be used as basis for future research.